Numerical Simulation of Mining-Induced Damage in Adjacent Tunnels Based on FLAC3D - Guorui Wang; Peixian Li; Qiang Wu; Ximin Cui; Zhixiang Tan (Advances in Civil Engineering)
The Bayueshan (BYS) tunnels are adjacent tunnels which comprise key engineering structures important for Yurong highway from Chongqing to Sichuan, China. The tunnels were established crossing over the old goafs of a coal mine. The tunnels have been damaged three times between 2014 and 2016. To evaluate the reasons for the damage, fast Lagrangian analysis of continua in three dimensions (FLAC3D) was used to simulate the underground coal-mine excavation yearly from 2012 to 2015. The simulation results show that the subsidence of the ground surface increased annually. The maximum subsidence of the left tunnel was 505 mm and that of the right tunnel was 512 mm. The excavation led to increase in the tunnels’ stress concentration. The simulations further show that uneven horizontal displacement and subsidence were the major factors in inducing tunnel construction defects. Poor geological conditions, water, and vehicle dynamic loads were also important factors that induced damage. Several engineering suggestions for ways to maintain the tunnels are given in this paper, and the research provides a reference for safety evaluation for tunnels crossing over an old goaf.